Social Media and Identity Formation: Content Analysis of Movie “Eighth Grade” - Herawati Herawati; Rustono Farady Marta; Hana Rochani G. Panggabean; Changsong Wang (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
Movie is regarded as a visual medium that offers a comprehensive presentation of a phenomenon in a defined time. This study employed a qualitative method to provide an interpretive paradigm on the movie titled “Eighth Grade” (directed by Bo Burnham, 2018). It aims to understand the massive role of the use of social media in shaping the identity of young people. The content analysis of movie “Eighth Grade” was carried out by considering abstraction, explication, and structuring. To understand this phenomenon, this study employed Luyckx's perspective on identity formation theory and the social identity model of deindividuation effect. The results of the research showed that the movie